The outlandish, the realistic, and the real: contextual manipulation and agent role effects in trolley problems - Gold, Natalie; Pulford, Briony D.; Colman, Andrew M. (Frontiers in Psychology, 2014)
Hypothetical trolley problems are widely used to elicit moral intuitions, which are employed in the development of moral theory and the psychological study of moral judgments. The scenarios used are outlandish, and some philosophers and psychologists have questioned whether the judgments made in such unrealistic and unfamiliar scenarios are a reliable basis for theory-building. We present two experiments that investigate whether differences in moral judgment due to the role of the agent, previously found in a standard trolley scenario, persist when the structure of the problem is transplanted to a more familiar context. Our first experiment compares judgments in hypothetical scenarios; our second experiment operationalizes some of those scenarios in the laboratory, allowing us to observe judgments about decisions that are really being made. In the hypothetical experiment, we found that the role effect reversed in our more familiar context, both in judgments about what the actor ought to do and in judgments about the moral rightness of the action. However, in our laboratory experiment, the effects reversed back or disappeared. Among judgments of what the actor ought to do, we found the same role effect as in the standard hypothetical trolley scenario, but the effect of role on moral judgments disappeared.